Effect of cold-resistant plasticizer with different acid chain lengths on the cold-resistant properties of PVC: Experiments and MD simulations - Xue Xu; Rujie Li; Li Gao; Beibei Sun; Hongming Liu; Shiai Xu (eXPRESS Polymer Letters)
As polyvinyl chloride (PVC) films are hard and brittle in a low-temperature environment, aliphatic dibasic acid ester plasticizers with different acid chain lengths were fabricated, i.e. di(2-ethylhexyl) adipate (DOA), di(2-ethylhexyl) sebacate (DOS) and dioctyl dodecanedioate (DOD), and their effects on the cold-resistant properties of PVC were investigated using experiments and molecular dynamics (MD) simulations. The brittleness temperature and tensile properties of plasticizers/PVC are negatively related to the acid chain length of the aliphatic dibasic acid esters. The brittleness temperatures of the three systems are all below –50 °C. In-situ low-temperature tensile tests and aging tests indicate that DOA/PVC exhibits the best cold resistance and stability. MD simulations further reveal that the best compatibility between DOA and PVC is attributed to its strong binding energy and weak hydrogen bonding interactions, while van der Waals forces are dominant in DOS/PVC and DOD/PVC. This study elucidates the structure-property relationship between aliphatic dibasic acid ester plasticizers and PVC from the perspective of molecular interactions, and provides insights into the design of cold-resistant PVC plasticizers.